Taguig Laboratory School of Innovation (TagLayIn) reimagining integrated school as 21st century learning environment for digital native learners - Tumala, Felicity M. (College of Architecture, University of the Philippines Diliman, 2025)
The architectural design of schools must evolve beyond its traditional rigidity to align with the demands of our dynamic, interconnected world. This transformation is particularly significant with the new educational reforms and teaching strategiesdesigned to address contemporary challenges in the Philippine education system. Furthermore, it must cater to the needs and preferences of the new generation learners — the digital-native learners. Guided by co-design Learning Environment Design (LED) framework, this study explored innovative design strategies to ensure flexibility & functionality, communality & individuality, and comfort & health, and conventionality & novelty through mixed method convergent design. Located in the DOST Compound in Taguig City, Taguig Laboratory School for Innovation (TagLayIn) is a a dual-purpose laboratory school with a psychosocial and tech-enhanced learning environment for digital native learners. And as a dual-purpose laboratory school, the school acts as a laboratory for 21st century formal and nonformal learning of students, especially with the integrated Science, Technology, Engineering, Arts, and Mathematics (STEAM) center, and a laboratory for teaching, research, and professional development in innovative pedagogies. Salient attributes of digital native learners such as preference for digital technologies, dynamic media and gamification, personalized learning, empoweredness, and vulnerability to mental health risks have also informed design translation. In conclusion, this project reimagined integrated K-10 school design to be an innovative learning environment that promotes 21st century learning and well-being of students and exemplify architecture’s role in addressing contemporary educational challenges.